The role of regulation, tradition and gender in doing business: case study and survey report on a two-year research project in Ghana - Aimée Hampel-Milagrosa (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Since the publication of the first Doing Business report in 2003, the World Bank managed to trigger a wave of policy reforms that paved the way for the streamlining of regulations affecting small and medium-sized companies worldwide. Through its rankings, Doing Business aims to expose and do away with cumbersome business regulations and make it easier, cheaper and faster to do business. Doing Business claims that efficient regulation will level the playing field between male and female entrepreneurs and that women would actually benefit from policy reforms with larger pay-offs. Building upon the argument that there is more to female entrepreneurship than regulation alone, this two-year study examines the interaction between business regulation and local tradition when women do business. Funded by the Danish International Development Agency (DANIDA) and the German Ministry for Economic Cooperation and Development (BMZ) the study focuses on Ghana, a consistent policy reformer in Africa, to look at issues of regulation, tradition, and entrepreneurial characteristics as well as present a number of recommendations on how to approach the highly disputed subject of gender in the Doing Business.
Keywords: 330; Unternehmer; Weibliche Führungskräfte; Selbstständige; Unternehmensgründung; Wirtschaftspolitik; Ghana